English for the college-bound high school student. (Las Cruces, NM : Pro One Software, 1995)
Multimedia High School Grammar, Multimedia Middle School Grammar, Multimedia Vocabulary, Multimedia English Composition
System requirements: IBM PC or compatible; CD-ROM drive; Windows 3.1 or better.
Keywords: English language -- Self-instruction.; English language -- Grammar; English language -- Computer-Assisted instruction; CD-ROMs.